Well Connected to Your Digital Object? E-Curator: A Web-based e-Science Platform for Museum Artefacts. - Hess, Mona; Simon Millar, Francesca; Robson, Stuart; MacDonald, Sally; Were, Graeme; Brown, Ian (Literary & Linguistic Computing, 2011)
This article describes the development of a new virtual research tool for the Arts and Humanities community. The E-Curator project led by Museums and Collections at University College London took a practical, multidisciplinary approach to traceable storage and transmission of three-dimensional (3D) laser scan data sets. The objective was to establish protocols for retrievable data acquisition and processing to facilitate remote web-based access to museum e-artefacts and thereby enhance international scholarship. An Internet capable 3D visualization tool was designed, using state-of-the-art colour laser scanning technology for digitizing museum objects in combination with an e-science developed data storage and retrieval solution (Storage Resource Broker). The prototype was developed in discussion with a team of museum curators and conservators who were able to compare the handling of a range of real objects with their virtual copies on-screen. This article will explore two case studies of objects recorded with an Arius3D colour laser scanner and a handheld Metris K-Scan laser scanner to illustrate the 3D recording methodology and highlight how the developed system is capable of complementing traditional cataloguing and analysis methods for museum artefacts and enable digital repatriation. Anthropological research, based on observations from the example of the E-Curator project, is discussing the production, reception, and circulation of 3D digital objects and the networked technology of the digital image.